2012
DOI: 10.1177/0300985812465325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling Reveals Prognostically Significant Subtypes of Canine Lymphoma

Abstract: We performed genomewide gene expression analysis of 35 samples representing 6 common histologic subtypes of canine lymphoma and bioinformatics analyses to define their molecular characteristics. Three major groups were defined on the basis of gene expression profiles: (1) low-grade T-cell lymphoma, composed entirely by T-zone lymphoma; (2) high-grade T-cell lymphoma, consisting of lymphoblastic T-cell lymphoma and peripheral T-cell lymphoma not otherwise specified; and (3) B-cell lymphoma, consisting of margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 31 publications
(60 reference statements)
8
112
1
3
Order By: Relevance
“…Boxers often develop lymphoblastic T-cell lymphomas as well as peripheral T-cell lymphoma (PTCL) (Lurie et al 2008), both aggressive forms of T-cell lymphoma (Frantz et al 2013), whereas golden retrievers are more prone to developing T-zone lymphomas that are relatively mild and have not been described in humans (Fosmire et al 2007;Seelig et al 2014). The typical mutation pattern in those two breeds is remarkably distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Boxers often develop lymphoblastic T-cell lymphomas as well as peripheral T-cell lymphoma (PTCL) (Lurie et al 2008), both aggressive forms of T-cell lymphoma (Frantz et al 2013), whereas golden retrievers are more prone to developing T-zone lymphomas that are relatively mild and have not been described in humans (Fosmire et al 2007;Seelig et al 2014). The typical mutation pattern in those two breeds is remarkably distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the limitations of small sample numbers, there were no obvious differences in clinical presentation or outcome between these 2 histologic subtypes. A recent paper examining gene expression profiles in a small number of canine lymphoma cases suggests that both PTCL and LBT have similar gene expression profiles and may represent a continuum of the same disease 26. Work comparing surface phenotype with the Kiel cytologic classification in a small subset of canine T‐cell lymphomas found that 5/8 small clear cell (T zone correlate) and 5/5 pleomorphic mixed small and large (PTCL correlate) tumors expressed surface CD4 4.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that this treatment would be most effective against a specific subset of DLBCL, such as EZH2-mutated GC DLBCL. It has been challenging to separate canine DLBCLs into activated B-cell (ABC) type and GC-type DLBCL 11, 53 , although one study suggested canine DLBCL might be more similar to human ABC type DLBCL 54 . Second, the study was designed to address chemosensitization of LPCs by valspodar, and the sample size was not powered to reveal if this protocol would significantly improve survival outcomes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…RNA prepared from biopsies obtained at diagnosis (Day 0) and on the fourth day of neoadjuvant treatment for enrolled dogs (Day 4) was quantified and assessed for quality as described 11, 22 . Briefly, total RNA was quantified using a fluorimetric RiboGreen assay and the total RNA integrity was assessed using capillary electrophoresis in the Agilent BioAnalyzer 2100 to generate RNA Integrity Numbers (RIN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation